Proximal row carpectomy in the third millenium: is it still a valid indication? - Pogliacomi, Francesco; Marenghi, Letizia; Corradi, Maurizio; Pedrazzini, Alessio; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2014)
Proximal row carpectomy (PRC), which was initially described by Stamm in 1944, is a surgical procedure for degenerative disorders of the proximal carpal row of the carpus. Despite the good results reported in the literature, this technique has been gradually replaced over the years by others considered more modern and actual, such as wrist arthroplasty and arthrodesis. In this context the authors performed the following study and analyzed retrospectively 14 patients who underwent PRC during an eighteen years period, between June 1996 and June 2013, in order to determine if this surgical operation can be considered still indicated. The results of this study confirm that PRC, more or less associated with the use of capsular flaps and/or osteochondral grafts, is nowadays a valid and simple procedure in selected patients, ensuring a satisfactory functional recovery and regression of pain.